Implementation Of Criminal Fines On State Financial Recovery In Violations Of Criminal Acts Of Excise To Support The Achievement Of Sustainable Development Objectives - Mega Tri Astuti Z; Lu Sudirman; Junimart Girsang (LEGAL BRIEF, 2022)
The results of this study indicate that criminal liability for the crime of selling excisable goods that are not attached to excise stamps is carried out by Saman actors based on the decision of the Batam District Court number with Case Number: 956/Pid.Sus/2017 /PN.Btm dated February 7, 2018 which is wrong One of the rulings handed down which reads as follows: To declare that the defendant SAMAN has been legally and convincingly proven guilty of committing a crime as regulated and is punishable by a criminal offense in the Single Indictment in violation of Article 54 of Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 regarding Excise and Imposing a criminal sentence against the defendant SAMAN in the form of a fine of Rp. 332,320,000,- (three hundred and thirty-two million three hundred and twenty thousand rupiah); provided that if the fine is not paid, it must be replaced with a prison sentence of 1 (one) year, this proves that the deterrent effect for perpetrators of criminal acts in the economic field is not fully imprisoned, and the interest of returning state losses due to violations that have been committed is more effective and efficient in order to restore leakage of state revenue resulting from the crime of selling cigarettes without being attached to excise stamps